Modelling of the operation of a Dual Mass Flywheel (DMF) for different engine-related distortions. Issue 6 (2nd November 2018) - Szpica, Dariusz
ABSTRACT: The application of Dual Mass Flywheels (DMF) was inspired by the need to reduce the level of vibrations generated by the drivetrain. The DMF input parameters are a result of the engine operation, in which the cyclicity of the subsequent strokes results in a variation of the engine speed. The fewer the cylinders the greater the engine speed variation and fluctuation of the engine torque. Additionally, the engine speed and torque variations are influenced by distortions, which is why the author attempted to develop a mathematical model of a DMF based on the motion equation. The methodology of calculations was also presented. For simplification, the moment of resistance generated by the drivetrain was assumed as constant. The simulation model checked out as correct and its sensitivity to small changes of the input parameters was confirmed. The mathematical description, despite simplifications, may find application in modelling of drivetrains fitted with DMF.